Standard blank for wood lamination on khaya ivorensis / Izzah Azimah Noh - Noh, Izzah Azimah (Faculty Of Applied Sciences, 2015)
This paper focuses on the standard blank for wood lamination on Khaya ivorensis. Standard blank is a cutting standard for a blank which is provides improving and increasing the value of sawn timber. Parameter for standard blank were machining practices and lamination process. Adhesives used for the study is Polyvinyl Acetate (PVAc). It has excellent dry adhesion, good gap-filling properties, fast setting, and colourless glue lines and ease of application. The purpose of standard blank based on machining practices (system) and lamination process (process). Explain that, the different machine used in producing sawn timber provides different result for surface roughness that affect the gluing properties during lamination process. The physical and mechanical properties were tested as Modulus of Rupture (MOR), Modulus of Elasticity (MOE), Compression shear and Delamination test were evaluated based on reference standard of in house method testing; BS 373:2008 (MOR and MOE), BS 373:1957- reconfirm 2008 (Compression shear) and JAS 1751 2008 (Delamination test). By using standard of variance (SOV) of the system for MOR is 1.298, MOE is 3.571 and result for compression shear of the system is 154.227. Meanwhile, the lamination results for MOR is 4.099, MOE is 0.638 and for compression shear is 47.33. Therefore, combination standard of variance for the system and lamination for MOR is 5.32, MOE is 6.426 and 4.832. As a results for physical and mechanical properties stated the MOE for lamination is significant compared to with sanding and without sanding system which is no significant differentiation at 95% confident of interval. For the compression shear, the results show system is highly significant compared to the lamination parameter.